the Teaching English as a Foreign Language in Inclusive School: Issues of Attention Deficit Hyperactivity Disorder (ADHD) Students: Challenges in Teaching English to Students with ADHD - Indrawati, Johara (The Progress: Journal of Language and Ethnicity, 2023)
This research sought to examine the difficulties encountered by educators and students with Attention Deficit Hyperactivity Disorder (ADHD) in the context of English language learning. Instructing students with ADHD presents a myriad of challenges, particularly in the realm of foreign language acquisition. Educators experience heightened stress levels in response to these challenges, as considerable energy and time are expended in addressing the unique needs of students with ADHD. Employing a descriptive qualitative research design, this study enlisted the participation of three educators responsible for fifth and eighth-grade classes within inclusive educational settings. Data were gathered through structured interviews with the educators, direct observation of the teaching and learning processes, and scrutiny of pertinent documents. The findings illuminated several challenges faced by English teachers, including time and energy constraints, emotional and behavioral issues, failure to meet educational targets, and a limited mastery of effective teaching methodologies. Notwithstanding the myriad challenges encountered, educators expressed a sense of satisfaction and joy in the process of teaching students with ADHD.